Cardiovascular health and physical activity among individuals with spinal cord injury - Totosy de Zepetnek, Julia (My University, 2014)
An increased prevalence and earlier onset of cardiovascular disease (CVD) occurs in persons with spinal cord injury (SCI); the higher risk may be explained by novel CVD risk factors of aerobic capacity and peripheral vascular structure and function. Physical inactivity likely contributes to the basis of increased CVD risk after SCI, however evidence on the effectiveness of exercise programs in attenuating CVD risk in SCI is insufficient. The present thesis evaluated novel CVD risk factors in a cohort of individuals with chronic SCI, and examined the effects of a single bout of exercise and exercise training on CVD risk. The first study demonstrated dramatic decreases in body composition, aerobic capacity, and sublesional endothelial function via flow-mediated dilation (FMD) in adults with chronic SCI vs. able-bodied (AB) controls. The second, third, and fourth studies assessed the role of shear rate (SR) patterns on FMD. Elevated retrograde SR had a detrimental effect on brachial and superficial-femoral-artery (SFA) FMD in both SCI and AB, but elevated anterograde SR had a favorable effect on SFA FMD in AB only. The fifth study demonstrated that sublesional vasculature does not respond to a 4-month combination aerobic and resistance-training program using the recently released physical activity guidelines for adults with SCI (PAG). The results of this thesis highlight the multilayered regulation of sublesional vasculature, and that it may respond differently to a single bout of exercise and exercise training when compared to an AB population. This information is crucial when designing strategies to combat impaired vascular structure and function after SCI. The results from this thesis also indicate the potential for the PAG to improve aspects of anthropometrics, body composition, and carotid vascular health in adults with SCI. Further investigations are necessary to delineate the effects of SCI itself, and of exercise, on CVD risk in this population.
Keywords: cardiovascular physiology; spinal cord injury; physical activity